The Deeds of Archbishops of Magdeburg: The Question Concerning the Works Book (Liber Gestorum) of Saint Bruno of Querfurt - Leonavčiūtė, Inga (Lietuvos istorijos studijos, 2015)
The article concerns the Brunonian scenes from the Deeds of Magdeburg Archbishops, written in the 30s-40s of the 12th century and continued till 1513, and their relationship with St. Bruno’s Work Book (Liber gestorum) mentioned in them, which, however, did not survive. Until the beginning of the 16th century, the Deeds of Magdeburg Archbishops were not only continued but also edited and supplemented in certain places while transcribing the manuscripts. In the 19th century, while publishing the Deeds of Magdeburg Archbishops, Wilhelm Schum used 15 manuscripts which were divided into two – A and B – wordings. After analyzing the Deeds of Magdeburg Archbishops it was determined that three Brunonian scenes happening in wording A were set as a single story in wording B. Having carried out the analysis of St Bruno’s Liber gestorum, it can be stated that there was a narrative in the A wording next to the Tagino period about St. Bruno Boniface who was a Canon of Magdeburg, was accepted to the King’s court, lived in an erem in Italy with the Saints Benedict and John, who received the pallium from the Pope, was ordained Archbishop of the pagans (tribes) by Tagino, the Archbishop of Magdeburg, and was tortured by them. The question concerning the dependence of the genealogical knowledge to St. Bruno’s Works Book remains open.The narrative about the St Bruno’s mission through Prague of Bohemia to Hungary, presented in the Deeds of Archbishops of Magdeburg, is the interpolation of B3 (out of it B3a) manuscripts of the 50s-60s of the 15th century and is not related to the narrative of liber gestorum. The story of St. Bruno, told in these manuscripts, is the summary based on Life and Martyrdom story found in manuscripts from Dessau (15th century) and Querfurt (16th century), which was already found in Collections of Saints of the 15th century.
Keywords: Saint Bruno of Querfurt; 1009; Hagiography; Deeds of Archbishops of Magdeburg; Book of the Deeds of St Bruno; The Life and Martyrdom of St. Bruno